Transformasi Teori Administrasi Pendidikan: Konsep, Implementasi, dan Tantangan dalam Mewujudkan Tata Kelola Pendidikan yang Efektif - Nuruddin; Meti Fatimah (TSAQOFAH, 2026)
The field of educational administration has undergone significant transformation in response to shifts in educational paradigms, advances in digital technology, the demands of globalization, and the growing need for effective, efficient, transparent, and accountable governance of educational institutions. Although educational administration has been widely discussed, studies integrating its theoretical development, implementation, and challenges within the context of educational governance in the digital era still require further strengthening. This article aims to examine the transformation of educational administration theories, their implementation in the management of educational institutions, and the various challenges involved in achieving high-quality educational governance. The study employed a library research method with a qualitative descriptive approach through an analysis of books, national and international journal articles, and relevant educational policy documents. The findings indicate that educational administration theories have developed from classical approaches oriented toward organizational efficiency to modern approaches emphasizing transformational leadership, school-based management, collaboration, innovation, digitalization, and data-driven decision-making. The implementation of educational administration in the digital era provides opportunities to improve the quality of educational services through the use of information technology, but it continues to face constraints, including limited human resource competencies, resistance to change, inadequate facilities and infrastructure, the digital divide, and a weak organizational culture. This study concludes that the transformation of educational administration requires strengthening leadership capacity, improving the competencies of educators and education personnel, digitalizing administrative systems, developing a quality culture, and fostering collaboration among stakeholders. These findings contribute to the development of educational administration studies and provide practical implications for educational institutions in establishing effective, adaptive, accountable, and sustainable governance.